Implementasi Media Interaktif dan One Day One Book untuk Menumbuhkan Minat Baca dan Pemahaman Teks di SDN Karangtengah 1 Ngawi - Rahmah, Dzakiyah Risya; Mujahidin Farid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low reading interest and text comprehension skills of students at SDN Karangtengah 1 Ngawi indicate the need for innovation in Indonesian language learning. This condition is caused by the limited variety of learning media used and the lack of consistent literacy practices. This study aims to explain the implementation of interactive media and the One Day One Book (ODOB) program as strategies to improve students’ reading interest and text comprehension. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, documentation, and field notes. Interactive media were used to create more engaging learning and encourage active student participation, while the ODOB program was implemented as a daily literacy activity to build reading habits. The results show that the use of interactive media and the ODOB program can enhance students’ learning motivation, engagement, reading interest, and text comprehension. These findings indicate that both strategies are effective in fostering a literacy culture at SDN Karangtengah 1 Ngawi.